The outcome of Tuberculosis control after application of the national TB program in Red Sea State, Sudan - bashir abdrhman bashir (Mediterranean Journal of Hematology and Infectious Diseases)
Background Tuberculosis (TB) is an endemic disease in Port Sudan city. Efforts to control this disease started in 1996 with the establishment of a national tuberculosis control committee. Field application of a national tuberculosis program (NTP) was implemented in Port Sudan by the ministry of health, according to the guidelines of the world health organization (WHO). Objective This study was aimed at evaluating the outcome of tuberculosis control after the application of this program. Design A retrospective study Patients and Methods The active TB cases admitted and treated in Port Sudan tuberculosis diagnostic center were studied. The outcome of control was evaluated, and comparison was made between years 2002 to 2010. Results The total number of TB cases increased from 521 in 2002 to 1174 in 2010. Detection rate decreased from 87% to 23%, and default decreased in 2007 (8%) and increased in 2009 (19%). However, there was an increase in the rate of therapy completion. And there was no change in the rate of treatment failure, and relapse or deaths. Conclusion Nevertheless, the completion rate slightly improved, the overall outcome of the application of the NTBP was not satisfactory. A recommendation for speedy improve the infrastructure accompanied by supporting material of the health care system to create a suitable successful program is essential.